PENDIDIKAN AGAMA KRISTEN DAN PEMBELAJARAN INKLUSIF DALAM KURIKULUM MERDEKA - Andy Saputra (CV. ADIBA AISHA AMIRA, 2024)
Christian Religious Education plays an essential role in shaping students' character based on values of love, tolerance, and care. On the other hand, inclusive learning emphasizes full access and participation for all students, including those with special needs and diverse backgrounds. The Merdeka Curriculum, with its focus on student-centered learning and character-building projects through the Profile of Pancasila Students (P5), offers opportunities for Christian Religious Education (CRE) to be integrated with inclusive principles. This study aims to analyze the integration of CRE and inclusive learning within the Merdeka Curriculum through a literature review approach. The research identifies several challenges and opportunities in implementing inclusive CRE. Key challenges include limited resources, teacher readiness, and the need to adjust materials to meet the diverse needs of students. However, significant opportunities exist, such as the potential of CRE to instill values of acceptance and love in a diverse educational environment. The study's implications include recommendations for schools and the government to strengthen teacher training, develop differentiated learning methods, and establish policies that promote collaboration between teachers and support staff. The findings are expected to serve as a reference for developing more inclusive and adaptive religious education within the Merdeka Curriculum. With proper integration, CRE not only functions as a cognitive subject but also as a means to build a school community that values and supports diversity. The study recommends periodic evaluations and continuous collaboration between teachers, schools, and policymakers to achieve more inclusive education rooted in Christian values.